Remarkable Homeostasis of Protein Sialylation in Skeletal Muscles of Hibernating Daurian Ground Squirrels (Spermophilus dauricus) - Dang, Kai; Yu, Han-Jie; Xu, Shen-Hui; Ma, Tian-Ran; Wang, Hui-Ping; Li, Yang; Li, Zheng; Gao, Yun-Fang (Frontiers in Physiology, 2020)
As the most common post-translational protein modification, glycosylation is intimately linked to muscle atrophy. This study aimed to investigate the performance of protein glycosylation in the soleus muscle (SOL) in Daurian ground squirrels (Spermophilus dauricus) and to determine the potential role of protein glycosylation in the mechanism underlying disuse muscle atrophy prevention. The results showed that (1) seven glycan structures comprising sialic acid α2-3 galactose (SAα2-3Gal) were altered during hibernation; (2) alterations in the SAα2-3Gal structure during hibernation were based on changes in the expression levels of beta-galactoside alpha-2 and 3-sialyltransferases; and (3) α2-3–linked sialylated modifications of heat shock cognate 70 and pyruvate kinase and expression of 14-3-3 epsilon protein were oscillatorily changed during hibernation. Our findings indicate that the skeletal muscles of hibernating Daurian ground squirrels maintain protein sialylation homeostasis by restoring sialylation modification during periodic interbout arousal, which might protect the skeletal muscles against disuse atrophy.